Elevated CO2 differentially affects the properties of grain from wild and domesticated rice. (July 2021) - Rahman, Sayedur; Copeland, Les; Atwell, Brian J.; Roberts, Thomas H.
Abstract: Interspecific germplasm from wild species of Oryza will be increasingly applied to breeding programs over the coming decades. However, the concurrent impact of rising atmospheric CO2 concentrations (atm-CO2 ) on grain properties is unknown. Wild accessions of Australian native rice species ( Oryza australiensis and O. meridionalis ) and the local cultivar ( O. sativa cv. Doongara) were grown to maturity in glasshouses at ambient (400 ppm; aCO2 ) and elevated (700 ppm; eCO2 ) atm-CO2 and physicochemical properties of the grains were compared. Seed length (Sl), seed width (Sw) and 1000-seed weight (TSW) were higher at eCO2 than aCO2, while nitrogen content (N) and apparent amylose content (AC) were not significantly changed, irrespective of genotype. Rapid viscosity analyser (RVA) profiles revealed increased peak viscosity (PV) for rice under eCO2, indicating differences in starch gelatinization. However, final viscosity (FV) increased in the wild rices in eCO2, whereas it decreased in Doongara. Increases in PV were accompanied by lower estimates of protein contents (PC) at eCO2 in all species. When AgNO3 was excluded from the RVA, it became apparent that its presence had enhanced the effects of eCO2 on flour pasting properties through inhibition of α-amylase activity of the flour. Our results suggest that grain morphology and pasting properties are differently affected by eCO2 in the wild rices compared with cultivated rice. These data will inform the breeding criteria for rice grain properties and inform the introgression of wild germplasm. Graphical abstract: Image 1 Highlights: Wild accessions and domesticated rice were grown at ambient and elevated CO2 (eCO2 ). Grain dimensions and weight were greater at eCO2 . Nitrogen content and apparent amylose content were unaffected by eCO2 . Starch gelatinization was altered by eCO2 as indicated by rapid visco analysis. Effects of eCO2 on specific grain properties were dependent on genotype.